ANALYSIS ON DIFFICULTIES OF EFL STUDENTS’ ARGUMENTATIVE PARAGRAPH WRITING - Purnama, Vonny (SPHOTA: Jurnal Linguistik dan Sastra, 2021)
In learning foreign language, writing skill is considered as the most difficult skill to be mastered by the English Foreign Learners (EFL) students. However, this skill is very needed to be learned by the higher education students. Therefore, this study aims to find out the difficulties of English Foreign Learners (EFL) students in argumentative writing. The data source of this study was the taken from the students’ argumentative writings. They were required to make an argumentative writing with certain topic. The theories writing and argumentative writing were used in this study and the result of the previous researcher in the same area was also used as the literature review. The finding shows that the difficulties of the students are in their linguistic used and critical thinking. In terms of linguistic difficulties, there were found the lack of word formation, punctuation, structure, tenses, and developing the content. Based on the findings, the lecturers should find a proper strategy in guiding the students to be able to improve their skill in argumentative writing skill.